Prediabetes and Type 2 Diabetes Are Associated With Generalized Microvascular Dysfunction: The Maastricht Study. Issue 18 (1st November 2016) - Sörensen, Ben M.; Houben, Alfons J. H. M.; Berendschot, Tos T. J. M.; Schouten, Jan S. A. G.; Kroon, Abraham A.; van der Kallen, Carla J. H.; Henry, Ronald M. A.; Koster, Annemarie; Sep, Simone J. S.; Dagnelie, Pieter C.; Schaper, Nicolaas C.; Schram, Miranda T.; et al.
Abstract : Background: Type 2 diabetes (T2DM) is associated with an increased risk of cardiovascular disease. This can be partly explained by large-artery dysfunction, which already occurs in prediabetes ("ticking clock hypothesis"). Whether a similar phenomenon also applies to microvascular dysfunction is not known. We therefore tested the hypothesis that microvascular dysfunction is already present in prediabetes and is more severe in T2DM. To do so, we investigated the associations of prediabetes, T2DM, and measures of hyperglycemia with microvascular function measured as flicker light-induced retinal arteriolar dilation and heat-induced skin hyperemia. Methods: In the Maastricht Study, a T2DM-enriched population-based cohort study (n=2213, 51% men, aged [mean±standard deviation] 59.7±8.2 years), we determined flicker light-induced retinal arteriolar %-dilation (Dynamic Vessel Analyzer), heat-induced skin %-hyperemia (laser-Doppler flowmetry), and glucose metabolism status (oral glucose tolerance test; normal glucose metabolism [n=1269], prediabetes [n=335], or T2DM [n=609]). Differences were assessed with multivariable regression analyses adjusted for age, sex, body mass index, smoking, physical activity, systolic blood pressure, lipid profile, retinopathy, estimated glomerular filtration rate, (micro)albuminuria, the use of lipid-modifying and blood pressure-lowering medication, and prior cardiovascular disease. Results: Retinal arteriolar %-dilation was (mean±standard deviation) 3.4±2.8 in normal glucose metabolism, 3.0±2.7 in prediabetes, and 2.3±2.6 in T2DM. Adjusted analyses showed a lower arteriolar %-dilation in prediabetes (B=–0.20, 95% confidence interval –0.56 to 0.15) with further deterioration in T2DM (B=–0.61 [–0.97 to –0.25]) versus normal glucose metabolism ( P for trend=0.001). Skin %-hyperemia was (mean±standard deviation) 1235±810 in normal glucose metabolism, 1109±748 in prediabetes, and 937±683 in T2DM. Adjusted analyses showed a lower %-hyperemia in prediabetes (B=–46 [–163 to 72]) with further deterioration in T2DM (B=–184 [–297 to –71]) versus normal glucose metabolism ( P for trend=0.001). In addition, higher glycohemoglobin A1c and fasting plasma glucose were associated with lower retinal arteriolar %-dilation and skin %-hyperemia in fully adjusted models (for glycohemoglobin A1c, standardized B=–0.10 [–0.15 to –0.05], P <0.001 and standardized B=–0.13 [–0.19 to –0.07], P <0.001, respectively; for fasting plasma glucose, standardized B=–0.09 [–0.15 to –0.04], P <0.001 and standardized B=–0.10 [–0.15 to –0.04], P =0.002, respectively). Conclusion: Prediabetes, T2DM, and measures of hyperglycemia are independently associated with impaired microvascular function in the retina and skin. These findings support the concept that microvascular dysfunction precedes and thus may contribute to T2DM-associated cardiovascular disease and other complications, which may in part have a microvascular origin such as impaired cognition and heart failure. Abstract : Supplemental Digital Content is available in the text.